A relational approach to the implementation of the European Landscape Convention in Sweden. (16th November 2016) - Dovlén, Sylvia
Abstract: The European Landscape Convention (ELC) aims to promote landscape protection, management and planning and to organise European cooperation on landscape issues. The introduction of the ELC in 2000 created a need for further theoretical work within the field of landscape research, which has historically provided a weak theoretical basis for policy implementation. In this study, a relational approach was used to investigate the ongoing ELC implementation process in Sweden, illustrating government dynamics and highlighting efforts to transform discourses and practices. The conceptual framework used comprised three analytical components (policy community, policy meaning and strategy-making practice) and the relational approach was applied at national, regional and local policy levels. The results revealed both progress and obstacles to ELC implementation in Sweden and confirmed the usefulness of the relational approach.